The Role of Asatidz Assistance in Shaping the Attitude of Tolerance of Pon-Pes An-Najah Students in the Religious Harmony Forum Assisted Village Tanjungrejo Jekulo Kudus - Edi Bahtiar; Any Umy Mashlahah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2025)
The An-Najah Islamic boarding school is a religious education institution located in Tanjungrejo Village, Jekulo District, Kudus Regency. Tanjungrejo Village is a village inhabited by a very diverse community, especially its religion. All religions are embraced by the population. The harmony of community life in the midst of religious diversity will be realized if all citizens have an attitude of tolerance among each other. So this research aims to explore the role of asatidz assistance in shaping the attitude of tolerance of Ponpes An-Najah students in the Assisted Village of the Religious Harmony Forum Tanjungrejo Jekulo Kudus. This type of research is a field research with a qualitative approach which is a research with natural situations using data collection techniques of observation, interviews, documentation, and FGDs. The data obtained were analyzed using data presentation, reduction, and conclusion. As the data obtained by the researchers that the fostering of tolerance attitude carried out by asatidz at An-Najah Islamic Boarding School, Tanjungrejo Village, Jekulo District, Kudus Regency is as follows: 1) Integrated in every book study which is routinely carried out every time after the maktubah prayer, especially when bandongan is active, namely bakda subuh, bakda magrib and bakda 'isyak; 2) Integrated in extra activities. namely: a) study of the book Riyadh ash-Shalihin which involves community members every Tuesday night; b) khithobah activities; c) deliberation activities; d) Qur'an tadarus activities; and e) incidental activities organized by local community members; 3) Incidental coaching activities. In addition, that the form of tolerance attitude assistance organized by asatidz towards students at An-Najah Islamic Boarding School, Tanjungrejo Village, Jekulo District, Kudus Regency is of two kinds, namely: 1) Individually through sorogan system learning activities or through special coaching for students who violate boarding school rules with moral and ethical material; and 2) In groups through bandongan learning activities, deliberations and so on. Based on these data, it can be analyzed that the role of asatidz assistance in fostering santri tolerance attitudes is sufficient. The mentoring pattern is structured and integrated in every activity in the pesantren.